2007
DOI: 10.1074/jbc.m610782200
|View full text |Cite
|
Sign up to set email alerts
|

Constitutively Active Parathyroid Hormone Receptor Signaling in Cells in Osteoblastic Lineage Suppresses Mechanical Unloading-induced Bone Resorption

Abstract: Multiple signaling pathways participate in the regulation of bone remodeling, and pathological negative balance in the regulation results in osteoporosis. However, interactions of signaling pathways that act comprehensively in concert to maintain bone mass are not fully understood. We investigated roles of parathyroid hormone receptor (PTH/PTHrP receptor) signaling in osteoblasts in unloading-induced bone loss using transgenic mice. Hind limb unloading by tail suspension reduced bone mass in wild-type mice. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…There were no significant changes in body weight in any of the groups during the course of the study. This confirmed that stress could be considered minimal in our experiments as previously described [Ishijima et al, 2001;Ono et al, 2007;Mizoguchi et al, 2008].…”
Section: Body Weightsupporting
confidence: 90%
See 2 more Smart Citations
“…There were no significant changes in body weight in any of the groups during the course of the study. This confirmed that stress could be considered minimal in our experiments as previously described [Ishijima et al, 2001;Ono et al, 2007;Mizoguchi et al, 2008].…”
Section: Body Weightsupporting
confidence: 90%
“…WT and MURF1 deficient mice were randomized regarding body weight into two groups. The two groups were subjected either to hind limb unloading (HU) or normal housing (loading) (NL) [Ishijima et al, 2001;Ono et al, 2007;Mizoguchi et al, 2008]. Mice were housed for at least 1 week prior to the study.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…bone formation and bone resorption. Systemic signals such as parathyroid hormone (PTH) 3 and vitamin D are the major regulators of the maintenance of bone mass and blood calcium (1)(2)(3). In addition, bone mass levels are also determined by a central nervous control through the activities of sympathetic tone on both bone formation and resorption sides (4 -7).…”
mentioning
confidence: 99%
“…PTH and osteocalcin concentrations are higher post-hibernation relative to prehibernation raising the possibility that anabolic actions of PTH may be important in maintenance of bone mineral content during hibernation [19]. Constitutive activation of PTH/PTHrP receptor signalling in osteoblasts, an action likely to mimic PTH administration, suppresses unloadinginduced bone loss in Col1a1-caPPR transgenic mice [20]. The anabolic effect of PTH on bone may in part relate to PTH mediated down-regulation of sclerostin expression by osteocytes [21].…”
Section: Discussionmentioning
confidence: 99%